ANALISI HUKUM TERHADAP PERKAWINAN DI BAWAH UMUR BERDASARKAN UU NO 16 TAHUN 2019 PERKAWINAN DI INDONESIA PENELITIAN - Napitupulu , Esrawati; Gabriel Siahaan, Parlaungan; Sitepu, Nazwa Sabila; Annisa , Nur; Pane, Sabrina Umami; Sesi Sihaloho , Tamara (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study analyzes the legal aspects of underage marriage in Indonesia based on Law Number 16 of 2019 concerning Marriage. The research aims to examine the effectiveness of legal regulations in preventing child marriage and to identify the factors causing the persistence of underage marriage practices in society. This study uses a library research method by examining various books, journals, laws, and scientific articles related to the topic. The data were analyzed through data reduction, presentation, and conclusion drawing techniques. The results show that although Law Number 16 of 2019 has equalized the minimum marriage age for men and women to 19 years, underage marriages still frequently occur due to economic conditions, low educational levels, cultural traditions, parental influence, and technological developments. In addition, the existence of marriage dispensation mechanisms through the court is considered a legal loophole that allows child marriage to continue legally. Underage marriage has negative impacts on children’s rights protection, including educational, psychological, biological, social, and legal consequences. Therefore, preventing child marriage requires not only stricter legal regulations but also community education, parental supervision, and changes in social and cultural values to provide better protection for children in Indonesia.